CONVENTIONAL GINGIVECTOMY FOR GINGIVAL ENLARGEMENT: A CASE REPORT - Triany Arnov, Steffi; Indah Rahmasari, Berliana; Rahmawati, Rizqika (Fakultas Kedokteran Gigi Unjani, 2025)
Gingival enlargement can occur due to many factors, ranging from systemically caused plaque to hormonal disorders, due to medications, orthodontic treatments and genetic diseases. This case report aims to describe the management of gingival enlargement using conventional gingivectomy. A 35-year-old male patient came to the hospital with complaints of rounded gums of the upper jaw. The patient reported no pain in his gums. One month after scaling and root planing, the patient underwent a gingivectomy on tooth 12. Evaluation three weeks after the procedure revealed no inflammation, reduction in enlargement, and improved oral hygiene. The determination of etiological factors is crucial in determining the appropriate actions for managing gingival enlargement. Gingivectomy is a procedure to eliminate gingival enlargement and make it easier for patients to maintain oral hygiene. To prevent recurrence in the future, patients need supportive periodontal therapy, which they should undergo regularly DOI : 10.54052/jhds.v5n2.p141-150